Factors influencing weight regain after weight loss programs: insights from recent studies - Annisa Farhah Ghinaa; Annisa Rizky Maulidiana (AcTion: Aceh Nutrition Journal, 2025)
Weight regaining is a challenge for most obese individuals who have successfully lost weight. Understanding the underlying factors contributing to weight gain is essential for developing more effective interventions. This study aimed to identify the factors contributing to weight gain in obese individuals after a weight loss program. A literature review was conducted using a narrative method following the PRISMA guidelines. The relevant international research articles used in this study were published in the last five years and retrieved from PubMed, ScienceDirect, and Wiley Online Library databases, resulting in the inclusion of nine studies that met the eligibility criteria, such as involving individuals with a history of weight loss programs, including dietary changes, physical activity, and cognitive behavioral therapy. The findings highlight multiple contributing factors to weight regain, including 1) loss of fat-free mass, 2) psychological, 3) behavioral and food environment factors, 4) weight loss history, 5) breakfast habits, 6) environmental contaminants, and 7) anti-obesity medication. Therefore, effective long-term weight management must consider these behavioral, metabolic, and environmental factors in obesity treatment programs to enhance their effectiveness in preventing weight regain.